Actitudes de los ciudadanos frente al crimen y al castigo: estudio piloto en la Universidad EAFIT, Medellín - Uribe Barrera, Juan Pablo (2013)
In order to justify an expansionist criminal policy, it is usual to appeal to the fact that this one responds to the popular claim, a social demand for security. However, current academic efforts in criminology have refuted this hypothesis. With wide empirical research, it has been proven that there isn’t a direct relationship between the punitive desires of society and the existing expansionist criminal policy and, likewise, public is not a monolithic block of punitive attitudes. Such research has not been developed yet in Colombia, even when in several occasions the exercise of the State’s punitive power has been extended to respond precisely to a supposed call from society, to the “get tough” trend requested against crime. The article shows some of the results of a research that proposes an empirical quantitative approach to a categorization of the Colombian attitudes toward crime and punishment through the development of a pilot study on the already referred topic at Universidad EAFIT. This one allows us questioning some assumptions that have been pivotal axes on this matter, mainly the one that could well be called “the myth of the punitive Colombians “, an idea often used to legitimize the current Colombian criminal policy. Para justificar una política criminal expansionista se apela a que la misma responde al clamor popular, a una demanda social de seguridad. Sin embargo, diversos esfuerzos académicos han rebatido tal hipótesis. Con amplia investigación empírica se ha demostrado que no existe una relación directa entre los deseos punitivos de la sociedad y la actual política criminal expansiva y que la ciudadanía no es un bloque monolítico de actitudes punitivas. Tal investigación no se ha desarrollado en Colombia, a pesar de que en repetidas ocasiones el ejercicio del poder punitivo del Estado se ha visto ampliado para responder precisamente a un supuesto llamado de la sociedad, a la “mano dura” que la misma exige frente al delito. El artículo enseña parte de los resultados de una investigación que propone un acercamiento empírico cuantitativo a la caracterización de las actitudes de los colombianos frente al crimen y al castigo mediante la elaboración de un estudio piloto sobre el referido tema en la Universidad Eafit. El mismo permite cuestionar algunas hipótesis que han surgido respecto a este tema, principalmente la que bien se podría denominar “el mito de los colombianos punitivos”, idea con la cual se suele legitimar la actual política criminal colombiana.